NEWS OF CONGRESS OF EUROPEAN SOCIETY OF CARDIOLOGY, VIENNA, SEPTEMBER 1-5, 2007 - S. Yu. Marcevich (Рациональная фармакотерапия в кардиологии)
News of Congress of European society of cardiology, Vienna, September 1-5, 2007.